Pengaruh Intensitas asset Biologis, Ukuran Perusahaan dan Konsentrasi Kepemilikan Manajerial Terhadap Pengungkapan Asset: - - Aliffatun, Annisa; saadah, lailatus - (JIATAX (Journal of Islamic Accounting and Tax), 2020)
This study aims to test and analyze the factors that influence the disclosure of biological assets. The factor studied include biological asset intensity, company size, and managerial ownership concentration. Analyzes the practice of disclosure of accounting in agriculture to biological assets based on PSAK 69: Agriculture. The study was conducted on 19 mining companies for 3 years (2016-2018) and the number of data as much as 57 samples were obtained using a purposive sampling technique. The collected data is analyzed using classical assumptions and multiple regression. Based on this study, it was concluded that of the three variables used in the study, there were two variables namely company size and managerial ownership concentration that affected the disclosure of biological assets. While the intensity of biological assets does not affect the disclosure of biological assets. Keywords: Biological Assets, Biological Asset Intensity, Company Size, Managerial Ownership Concentration, Biological Asset Disclosure.